2010
DOI: 10.1021/ja106212w
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Active Ligand-Mediated Oxidative Addition and Reductive Elimination at Square Planar Cobalt(III): Multielectron Reactions for Cross-Coupling

Abstract: Square planar cobalt(III) complexes with redox-active amidophenolate ligands are strong nucleophiles that react with alkyl halides, including CH(2)Cl(2), under gentle conditions to generate stable square pyramidal alkylcobalt(III) complexes. The net electrophilic addition reactions formally require 2e(-) oxidation of the metal fragment, but there is no change in metal oxidation state because the reaction proceeds with 1e(-) oxidation of each amidophenolate ligand. Although the four-coordinate complexes are ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(118 citation statements)
references
References 27 publications
5
112
0
1
Order By: Relevance
“…Intriguing examples from synthetic chemistry are Co III complexes ligated with two redox-active (“noninnocent”) amidophenolate ligands. 153 The complex can undergo oxidative addition reactions, without changing the oxidation state of the cobalt. Electrons flow to the redox-active ligands and are stored temporarily.…”
Section: C–c Bond-forming Reactions Involving Co and Co2mentioning
confidence: 99%
“…Intriguing examples from synthetic chemistry are Co III complexes ligated with two redox-active (“noninnocent”) amidophenolate ligands. 153 The complex can undergo oxidative addition reactions, without changing the oxidation state of the cobalt. Electrons flow to the redox-active ligands and are stored temporarily.…”
Section: C–c Bond-forming Reactions Involving Co and Co2mentioning
confidence: 99%
“…The metal center maintains its formal 3 + oxidation state with an intermediate spin with each aminophenolate providing one electron to afford the corresponding [Co III (iminosemiquinone) 2 (CH 2 CH 3 )] (12). [21] The metal formally maintains the same oxidation state in both oxidative addition and reductive elimination steps. Subsequent treatment of 12 with an organozinc compound leads to the cross-coupling product, reminiscent of a reductive elimination step (Scheme 5 a); however, this reaction is not yet catalytic.…”
Section: Redox Active Ligandsmentioning
confidence: 99%
“…[25] Soper and co-workers recently showed that metal-carbon bond formation can occur via metal-centered oxidative addition steps but without changing the d-electron configuration of the metal. [26] This was made possible by using redox active ligands that offer selective and fast electron transfer to the metal. The particular Co III complex, which is a square-planar Co III species (Scheme 3), featured two robust, redox noninnocent amidophenolate ligands.…”
Section: Redox Noninnocent Systemsmentioning
confidence: 99%